Analysis of an electrical impedance spectroscopy system in short‐term digital dermoscopy imaging of melanocytic lesions. (11th October 2017) - Rocha, L.; Menzies, S.W.; Lo, S.; Avramidis, M.; Khoury, R.; Jackett, L.; Guitera, P.
Summary: Background: Electrical impedance spectroscopy (EIS) is a noninvasive diagnostic technique that measures tissue impedance. Objectives: To evaluate the effect of adding an EIS measurement at baseline to suspicious melanocytic lesions undergoing routine short‐term sequential digital dermoscopy imaging (SDDI). Methods: Patients presented with suspicious melanocytic lesions that were eligible for short‐term SDDI (with no clear feature of melanoma on dermoscopy). EIS measurement was performed at the first visit following dermoscopic photography. Normally, an EIS score of ≥ 4 is considered positive; however, this protocol investigated a higher cut‐off in combination with SDDI. When the EIS score was ≥ 7 the lesion was excised immediately owing to the high risk of melanoma. Lesions with a score < 7 were monitored with standard SDDI over a 3‐month period. Results: From a total of 160 lesions analysed, 128 of 154 benign lesions received an EIS score of 0–6, giving a specificity of the EIS method for the diagnosis of melanoma of 83·1% [95% confidence interval (CI) 76·3–88·7]. Five of the six melanomas found in this study had an EIS score ≥ 7, with a sensitivity for melanoma diagnosis of 83·3% (95% CI 35·9–99·6). When EIS 0–6 lesions were subsequently followed up with SDDI, one additional melanoma was detected (EIS = 6) giving a sensitivity for the diagnosis of melanoma overall of 100% (95% CI 54·1–100; six of six malignant melanomas excised) and a specificity of 69·5% (95% CI 61·5–76·6; 107 of 154 benign lesions not excised). Conclusions: If utilizing a protocol where an EIS score ≤ 3 requires no SDDI and ≥ 7 requires immediate excision, it reduced the need for SDDI by 46·9% ( n = 75/160; 95% CI 39·0–54·9). Abstract : What's already known about this topic? Short‐term sequential digital dermoscopy imaging (SDDI) allows the detection of dermoscopically featureless melanoma but requires a delay in diagnosis. Electrical impedance spectroscopy (EIS) has a high sensitivity for the diagnosis of melanoma but a suboptimal specificity. What does this study add? By combining EIS at baseline with SDDI there was a reduced need to proceed to SDDI in just under half of cases. Linked Comment: Tromme. Br J Dermatol 2017; 177 :1166–1167 .